Crisis in the East of Ukraine: end or beginning of regional labour market development? - Olena Khandii; Inna Semenenko (Institute of Economic Research (IER), 2017)
Research background: Armed conflict and political crisis in Ukraine resulted in significant economy decline, caused migration inside the country and unemployment, changed Ukrainian labour markets. The questions arise, if these changes bring only negative effects and if there is a chance for economy revival. Purpose of the article: The purpose of the article is to examine changes in economy structure, present state of labour market in Donetsk and Luhansk regions, changes in demography situation; reveal the main tendencies and give recommendations concerning further development of labour market of the regions. Methodology/methods: The statistical information from the State Statistics Service of Ukraine, reports of International and other organizations have been analysed. Such methods as statistical and economic analysis, abstract-logical analysis, classification and systematization have been used. Findings & Value added: The population of the Eastern regions of Ukraine decreased under the influence of natural decrease and internal migrations. The internally displaced persons lost their jobs, and now they are suffering hard to survive. Many of them have to change their professions and acquire brand new skills and knowledge to become competitive. The majority of internally displaced persons are young people aged less than 30 years old. Their survival and survival of the regions are possible only on condition of existing desire of people to self-develop and self-organize. Thus small and medium enterprises and entrepreneurs start to appear in Donetsk and Luhansk regions. They substitute the existing huge industrial plants and become the main direction for labour market development in the East of Ukraine. Creation of small businesses is fully supported not only by government bodies, but also by International organizations. Assistance of international organizations should give the impetus for the search of new areas for growth and forms of interaction with the existing government and business.
Keywords: D74; J20; J60; O15; 330; labour market; small and medium business; migration; internally displaced person; crisis